Outstanding Questions in Magnetospheric Plasma Physics: The Pollenzo View - Stepanova, M (Elsevier Ltd, 2020)
Based on discussions held at a workshop in Bra-Pollenzo, Italy, this paper elaborates upon 19 outstanding questions of plasma physics in the Earth s magnetosphere. The questions are grouped according to (a) driving processes, (b) radiation belt and ring current issues, (c) auroral physics, (d) internal plasma processes, and (e) magnetosphere-ionosphere mapping issues. Future needs for magnetospheric plasma physics (measurements, techniques, simulations, theories, studies) are outlined. © 2020